Banks' Advantage in Hedging Liquidity Risk: Theory and Evidence from the Commercial Paper Market - GATEV, EVAN; STRAHAN, PHILIP E. (Journal of Finance, 2006)
ABSTRACT Banks have a unique ability to hedge against market‐wide liquidity shocks. Deposit inflows provide funding for loan demand shocks that follow declines in market liquidity. Consequently, banks can insure firms against systematic declines in liquidity at lower cost than other institutions. We provide evidence that when liquidity dries up and commercial paper spreads widen, banks experience funding inflows. These flows allow banks to meet loan demand from borrowers drawing funds from commercial paper backup lines without running down their holdings of liquid assets. We also provide evidence that implicit government support for banks during crises explains these funding flows.